Assessing Resources Devoted to Electronic Reporting and Automation Among Central Cancer Registries Meeting National Program of Cancer Registries (NPCR) Quality Standards - Tangka, Florence K. L.; Beizer, Jenny; Cole-Beebe, Maggie; Bernacet , Amarilys; Brown, Stephen; Pordell, Paran; Wilson, Reda; Subramanian, Sujha (Journal of Management Policy and Practice, 2024)
The Centers for Disease Control and Prevention (CDC) has emphasized a need for data modernization initiatives (DMIs) to improve the quality and timeliness of cancer surveillance data. To guide such DMI efforts, we need data on the resources required to generate high-quality data. Twenty-one central cancer registries (CCRs) collected data from July 2020 to June 2021. We explored the potential relationship between resources for (1) electronic reporting and automation and (2) the quality of CCR data. We then compared activity-based costs of registries that always (n = 8), sometimes (n = 6), or seldom/never (n = 7) met data quality standards for completeness, timeliness, duplicate rate, and missing values. We found the registries that consistently met data quality standards used more resources on setting up processes to acquire data, training staff, and processing data. Compared to high-quality registries, registries that seldom/never met quality standards spent the most on case finding/data abstraction of non-hospital records. This study provides key findings for resource use, which can guide advancements when implementing electronic reporting and automation to improve CCR operations.